2019
DOI: 10.1002/mabi.201970003
|View full text |Cite
|
Sign up to set email alerts
|

3D Microfibrous Scaffolds Selectively Promotes Proliferation and Glial Differentiation of Adult Neural Stem Cells: A Platform to Tune Cellular Behavior in Neural Tissue Engineering

Abstract: Front Cover: Three‐dimensional microfibrous scaffolds with varying topographies are fabricated using a microfluidic technique to investigate differentiation of neural stem cells. Scaffolds increased proliferation and glial differentiation, showing great potential for biomaterial‐based cell delivery strategies. This is reported by Bhavika B. Patel, Farrokh Sharifi, Daniel P. Stroud, Reza Montazami, Nicole N. Hashemi, Donald S. Sakaguchi in article https://doi.org/10.1002/mabi.201800236.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…On the other hand, scaffolds made from biocompatible materials may provide structural support for cell adhesion, proliferation, and differentiation mimicking the cellular microenvironment. A number of scaffolds made from solid [ 3 , 4 , 5 ], microfibrous materials [ 6 ], or gels [ 7 ] have been previously described to support the proliferation and localized differentiation of murine neural stem cells, indicating their potential value for neural tissue regeneration [ 8 ]. Among them, 3D foam biomaterials provide efficient cell adhesion, proliferation, and differentiation due to their unique properties (e.g., high surface-to-volume ratio, 3D porous structure) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, scaffolds made from biocompatible materials may provide structural support for cell adhesion, proliferation, and differentiation mimicking the cellular microenvironment. A number of scaffolds made from solid [ 3 , 4 , 5 ], microfibrous materials [ 6 ], or gels [ 7 ] have been previously described to support the proliferation and localized differentiation of murine neural stem cells, indicating their potential value for neural tissue regeneration [ 8 ]. Among them, 3D foam biomaterials provide efficient cell adhesion, proliferation, and differentiation due to their unique properties (e.g., high surface-to-volume ratio, 3D porous structure) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Highly tunable surface topography for hydrogel microfibers will be of particular interest in research endeavors where cells are being seeded onto the surface of microfibers, since surface topography is known to affect cell proliferation, differentiation, and overall health [3,6,7]. Cells are greatly affected by their microenvironment, and this simple method to modify microfiber surface topography can be utilized to provide an additional degree of control over the behavior of cells, adding another level of control in a powerful manufacturing process to create continuous and tunable hydrogel microfibers.…”
Section: Discussionmentioning
confidence: 99%
“…Their favorable attributes stem from their high surface-to-area ratio, rapid diffusion gradients and strong potential for biocompatibility [1][2][3]. Their contributions to biomedical fields thus far have included the encapsulation or seeding of bioactive molecules [4,5], cells [1,[6][7][8], or bacteria [9]; furthermore, their properties allow for the creation of a microenvironment that mimics conditions within the body, providing an extracellular-matrix (ECM) inspired scaffold for arranging and guiding cell growth, proliferation and differentiation [1,3,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo results demonstrated that this hydrogel promotes SCI mouseendogenous neurogenesis and functional recovery by restoring interrupted spinal cord circuits. PCL can mimic the structure of gray or white matter and promote the differentiation of NSCs to oligodendrocytes and the formation of axonal myelin sheaths, it is an ideal material in SCI tissue engineering (Donoghue et al, 2013;Patel et al, 2019). Wong et al (2008) implanted PCL into an animal model of total transection of SCI, and its open microchannel structure facilitates axon regeneration and myelination.…”
Section: Hydrogel Therapy Alonementioning
confidence: 99%